Integrating Strategies of Herbal Metabolomics, Network Pharmacology, and Experiment Validation to Investigate Frankincense Processing Effects - Ning, Zhangchi; Wang, Chun; Liu, Yuanyan; Song, Zhiqian; Ma, Xinling; Liang, Dongrui; Liu, Zhenli; Lu, Aiping (Frontiers in Pharmacology, 2018)
In-depth research on processing can promote the globalization of processed herbs. The purpose of this study is to propose an improved strategy for processing effect investigation. Frankincense and processed frankincense were used as research subjects. First, high-speed countercurrent chromatography (HSCCC) and preparation high-performance liquid chromatography (PHPLC) techniques were used for major compounds isolation and minor compounds concentration. Processed frankincense was subjected to two stepwise solvent systems, namely, n-hexane:ethanol:water (6:5:1) and n-hexane:methyl-acetate:acetonitrile:water (4:4:3:4), to yield 12 fractions, and 18 compounds were further separated. Second, a comprehensive metabolomic analysis conducted by ultrahigh-performance liquid-chromatography/electrospray-ionization mass spectrometry (UHPLC-Qtof-MS) coupled with multivariate statistics was performed to fully characterize the chemical components and discover the potential biomarkers between frankincense and processed frankincense. In total, 81 metabolites, including the 18 separated compounds, were selected as potential biomarkers between frankincense and processed frankincense among 153 detected compounds for their VIP values of greater than one. The tirucallane-type compounds and components with 9,11-dehydro structures clearly occurred at high levels in the processed frankincense, while lupine-type compounds and those with 11-keto structures were significantly higher in frankincense. Then, a network pharmacology model was constructed to decipher the potential mechanisms of processing. Intestinal absorption properties prediction indicated the possibility of processing-related absorption enhancement. A systematic analysis of the constructed networks showed that the C-T network was constructed with 18 potential biomarkers and 69 targets. TNF and IL-1β were among the top-ranked and were linked by 8 and 7 pathways, which were mainly involved in inflammation. The arachidonic acid metabolism pathway exhibited the highest number of target connections. Finally, the prediction was validated experimentally by an intestinal permeability and efficacy assay. The experiments provided convincing evidence that processed frankincense harbored stronger inhibition effects toward TNF-α-, IL-1β- and arachidonic acid-induced platelet aggregation. The processing procedure leads to changes of the chemical metabolites, which triggers the enhancement of absorption and cure efficiency. The global change of the metabolites, absorption and pharmacological effects of processing were depicted in a systematic manner.